Cover Feature: On the Action of General Anesthetics on Cellular Function: Barbiturate Alters the Exocytosis of Catecholamines in a Model Cell System (ChemPhysChem 10/2018). Issue 10 (22nd May 2018) - Ye, Daixin; Ewing, Andrew
Abstract : The Cover Feature illustrates the main mechanism of signal transduction and neuronal communication, exocytosis. In our arcticle, we use disk electrodes placed on top of PC12 cells to show that treatment with barbiturate induces fewer molecules released during exocytosis and changes the event dynamics. More information can be found in the Article by D. Ye and A. Ewing onpage 1173 in Issue 10, 2018 (DOI:10.1002/cphc.201701255 ).